Effects of Repeated, Long-Duration Hyperoxic Water Immersions on Neuromuscular Endurance in Well-Trained Males - Myers, Christopher M.; Kim, Jeong-Su; McCully, Kevin K.; Florian, John P. (Frontiers in Physiology, 2019)
PURPOSE: This study examined the effects of repeated long-duration hyperoxic water immersions (WI)s at 1.35 atmospheres absolute (ATA) on neuromuscular endurance performance. We hypothesized that over a five-day period of consecutive, resting, long-duration hyperoxic WIs there would be a decrease to neuromuscular endurance performance and tissue oxygenation with the quadriceps muscle, but not with the forearm flexors. METHODS: Thirteen well-trained, male subjects completed five consecutive 6-hour resting WIs with 18-hour surface intervals during the dive week while breathing 100% oxygen at 1.35 atmospheres absolute (ATA). We assessed skeletal muscle endurance performance before and after each water immersion (WI), and 24 and 72 hours after the final WI. Muscular endurance assessments included 40% maximal handgrip endurance (MHE) and 50-repetition maximal isokinetic knee extensions. Near infrared spectroscopy (NIRS) was used to measure muscle oxidative capacity (MOC) of the vastus lateralis and localized muscle tissue oxygenation of the vastus lateralis and flexor carpi radialis. Simultaneously, we measured brachioradialis neuromuscular activation by surface electromyography (SEMG). RESULTS: MHE time-to-fatigue performance declined by 15% at WI 3 (p = 0.009) and by 17% on WI 5 (p = 0.002). Performance continued to decline by 22% at 24-hours post-WI (p < 0.001) and by 12% on 72-hours post-WI (p = 0.019). 50-repetition IK knee extension total work decreased by 5% (p = 0.002) on WI 3, and was further reduced by 7.5% and 12.3% (p=0.032) at pre-WI 5 and 24-hours post-WI, respectively. However, the rate of fatigue was 8% (p=0.033) and 30% (p = 0.017) lower at WI 3 and 24-hours post-WI when compared to WI 1, respectively, demonstrating the muscles were still fatigued from the previous hyperoxic WIs. We detected no significant limitations in oxygen off-loading kinetics during the exercise or MOC measurements. CONCLUSION: Repeated, resting, long-duration hyperoxic WIs caused significant reductions to muscular endurance but not to indirect measures of oxygen kinetics in load bearing and non-load bearing muscles.